How Often Do You Think About Your Relationship With Nature? The Measurement of Environmental Identity Salience and Its Relationship With Proenvironmental Behaviors - Rahmani, Leïla; Haasova, Simona; Czellar, Sandor; Clergue, Valentina; Martin, Christian (Frontiers in Psychology, 2022)
Extant research finds that environmental identity is an important motivational factor for proenvironmental behavior. However, studies typically focus on investigating the effects of the strength of this identity. Based on insights from identity research, we theorize that the influence of individuals’ environmental identity on their proenvironmental behavior may depend on other identity dimensions as well. We argue that the frequency of activation of environmental identity in relevant life domains – environmental identity salience – may predict proenvironmental behavior beyond what environmental identity strength can explain. To test our theorizing, we propose a parsimonious measure of environmental identity salience. In four empirical studies, we establish that the new measure has sound psychometric properties in terms of internal consistency and discriminant validity with regard to measures of environmental identity strength. Importantly, our measure of environmental identity salience reliably predicts a range of self-reported and actual proenvironmental behaviors beyond the effects of environmental identity strength. In line with theoretical predictions, our data suggests that environmental identity salience and strength are related but distinct constructs. We conclude that investigating the nature and effects of environmental identity salience leads to a fruitful path to a more comprehensive understanding of proenvironmental behavior. The proposed new measure may serve as a helpful tool in this endeavor.